Comparison of clinical efficacy of hyperbaric ropivacaine with hyperbaric bupivacaine in spinal anesthesia for transurethral resection of prostate: A randomized and double-blind study - Savita Gupta,; Isha Yadav,; Anupriya Saxena,; Satendra Kumar, (Asian Journal of Medical Sciences, 2024)
Background: Ropivacaine is an ammino-amide local anesthetic agent with properties similar to bupivacaine, but its decreased lipophilicity is associated with reduced incidence of central nervous system toxicity and cardiotoxicity. This study evaluated the safety, efficacy, effects on hemodynamics and complications of spinal anesthesia using 0.5% hyperbaric bupivacaine and 0.75% hyperbaric ropivacaine in patients undergoing transurethral resection of the prostate (TURP). Aims and Objectives: The aim was to evaluate the safety, efficacy, hemodynamic stability, and side effects of spinal anesthesia using 0.5% hyperbaric bupivacaine and 0.75% hyperbaric ropivacaine in patients undergoing TURP. Materials and Methods: Sixty adult patients with physical status classes I and II, as determined by the American Society of Anesthesiologists, scheduled to undergo elective transurethral resection of prostate, were randomly allocated to receive either hyperbaric ropivacaine 0.75% 2.8 mL plus fentanyl 15 mcg or hyperbaric bupivacaine 0.5% 2.8 mL plus fentanyl 15 mcg. The parameters, such as demographic characteristics, duration of surgery, onset of sensory and motor blockade, hemodynamic stability, and complications, were compared in both groups. Results: Hyperbaric ropivacaine exhibited significantly slower onset times for sensory and motor blockade compared to hyperbaric bupivacaine. Patients in the ropivacaine group demonstrated better hemodynamic stability and experienced less hypotension compared to those who received bupivacaine. Moreover, the sensory and motor block lasted significantly longer in the bupivacaine group. Conclusion: About 0.75% hyperbaric ropivacaine is a better choice for spinal anesthesia in elderly patients undergoing TURP as compared to 0.5% hyperbaric bupivacaine.